The Land of the English Kin Studies in Wessex and Anglo-Saxon England in Honour of Professor Barbara Yorke - Langlands, Alexander James (Brill's Series on the Early Middle Ages, 2020)
Twenty-nine studies, covering a wide range of themes, present the most up-to-date thinking on the history, archaeology and toponymy of Anglo-Saxon England, with particular attention to Wessex, in honour of Professor Barbara Yorke. ; Readership: This book will appeal to historians, archaeologists and place-name scholars of the early medieval period and those interested in more specifically in the Anglo-Saxon world and the kingdom of Wessex.